CCD OBSERVATIONS OF THE INTERMEDIATE POLAR MU CAM AND GSC 04370-00206 - Chinarova, L. L.; Andronov, I. L.; Gubin, E. G. (Одеські астрономічні публікації, 2010)
Results of CCD observations of MU Cam and GSC 04370-00206 obtained at the 60 cm tele- scope of the RSI \Astronomical Observatory" of the Odessa National University. Variable stars: intermediate polars; eclipsing.